The Factor Structure of Polish Personality‐Descriptive Adjectives: An Alternative Psycho‐lexical Study. Issue 3 (1st May 2013) - Gorbaniuk, Oleg; Budzińska, Anna; Owczarek, Martyna; Bożek, Ewelina; Juros, Karol
Abstract The results of the Polish psycho‐lexical study have been included in nearly all comparisons aimed at finding dimensions common to various cultures and languages. Because of the ambiguity concerning the interpretation of some factors and because of a number of methodological shortcomings, it was decided that another lexical study of the Polish language should be carried out. The alternative study was based on more extensive lexical material and involved a sample covering the full age range. The analyses used 547 personality‐descriptive adjectives and self‐ratings from 624 respondents aged from 16 to 80 years (mean age = 38.0 years). In a six‐factor solution, the obtained structure was typical for many languages: Agreeableness, Extraversion, Conscientiousness, Emotional Stability, Honesty and Intellect. The result of factor analysis depended on neither the type of factoring nor the type of rotation applied. The results of the study were discussed in relation to cross‐language studies and to previous studies of the structure of Polish personality‐descriptive lexicon. Copyright © 2013 John Wiley & Sons, Ltd.